A numerical–experimental assessment of wall impingement models for spark-ignition direct-injection engines. (February 2020) - Grover, Ronald O; Fansler, Todd D; Lippert, Andreas; Drake, Michael C; Assanis, Dennis N
Liquid wall impingement in direct-injection engines can cause soot and hydrocarbon emissions as well as reduced combustion efficiency. This study focuses on detailed evaluations of numerical droplet impingement criteria that govern the onset of splash. The five selected splash criteria, which all extrapolate from single-droplet impacts to full sprays, are representative of those currently in use for spark-ignition direct-injection engines. The computations examined the sensitivity of impinging spray simulations to the splash criteria for a high-pressure, direct-injection swirl spray under atmospheric conditions impinging at a 45° angle onto a flat plate. The numerical results were compared to an unusually extensive set of experimental data: Mie scattering and light transmission imaging, plus quantitative refractive index matching measurements of the fuel film area and thickness, and phase Doppler interferometry measurements of droplet size and velocity near the plate. Good qualitative and at least fair quantitative agreement was obtained for the global spray impingement and wall film formation, especially for single-drop criteria that include the effect of viscosity. The film area and shape were insensitive to the splash criteria, illustrating the importance of film thickness measurements for validating simulations. The results also revealed the sensitivity of impingement calculations to droplet arrival frequency when that is taken into account. In general, the comparisons indicated the need to capture the effect of multiple droplets impinging on the wall at irregular frequencies in the criterion, as well as other important physics of the droplet–wall interaction that may mask the true effect of the impingement criterion.